IT resources and IT capabilities as a driver of physical infrastructure projects performance - Molina Cuellar, Luis G. (Pontificia Universidad Católica del Perú, 2018)
This study evaluates how Information Technology (IT) creates value in the performance of physical infrastructure (PI) projects. The research model is based on the concept of the Business Value of Information Technology (BVIT) and relates the integration of IT resources with the development of IT capabilities to promote the performance of PI projects. The model is evaluated empirically from first-hand data collected from surveys in public and private organizations whose core is the development of PI projects in Colombia. The empirical test indicates there is a strong relationship between IT and PI performance when the effects of IT resources and capabilities are mediated through the underlying mechanisms composed by IT support for competitive strategies and core competencies. The strong correlation between predictor constructs and PI project performance is confirmed upon calculating the total effects, after which the empirical results shall confirm the theoretical basis. The study includes managerial traits like moderator variables and empirical results indicate there are no heterogeneity issues. When countries achieve a foundational level of physical infrastructure, namely in basic services (i.e. water supply and sanitation), infrastructure for life and coexistence (i.e. housing, education, health, etc.) and ports and transport systems, they promote their national productivity and competitive edge, in turn increasing their social positions in relation to equity and sustainability. These transversal and relevant effects in the social context suggest to develop new studies in this field
Keywords: Tecnologías de la información; Infraestructura (Economía) -- Colombia; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04